Compartment-specific immunity in the human gut: properties and functions of dendritic cells in the colon versus the ileum. Issue 2 (9th February 2015) - Mann, Elizabeth R; Bernardo, David; English, Nicholas R; Landy, Jon; Al-Hassi, Hafid O; Peake, Simon TC; Man, Ripple; Elliott, Timothy R; Spranger, Henning; Lee, Gui Han; Parian, Alyssa; Brant, Steven R; et al.
Abstract : Objective: Dendritic cells (DC) mediate intestinal immune tolerance. Despite striking differences between the colon and the ileum both in function and bacterial load, few studies distinguish between properties of immune cells in these compartments. Furthermore, information of gut DC in humans is scarce. We aimed to characterise human colonic versus ileal DC. Design: Human DC from paired colonic and ileal samples were characterised by flow cytometry, electron microscopy or used to stimulate T cell responses in a mixed leucocyte reaction. Results: A lower proportion of colonic DC produced pro-inflammatory cytokines (tumour necrosis factor-α and interleukin (IL)-1β) compared with their ileal counterparts and exhibited an enhanced ability to generate CD4 + FoxP3 + IL-10 + (regulatory) T cells. There were enhanced proportions of CD103 + Sirpα − DC in the colon, with increased proportions of CD103 + Sirpα + DC in the ileum. A greater proportion of colonic DC subsets analysed expressed the lymph-node-homing marker CCR7, alongside enhanced endocytic capacity, which was most striking in CD103 + Sirpα + DC. Expression of the inhibitory receptor ILT3 was enhanced on colonic DC. Interestingly, endocytic capacity was associated with CD103 + DC, in particular CD103 + Sirpα + DC. However, expression of ILT3 was associated with CD103 − DC. Colonic and ileal DC differentially expressed skin-homing marker CCR4 and small-bowel-homing marker CCR9, respectively, and this corresponded to their ability to imprint these homing markers on T cells. Conclusions: The regulatory properties of colonic DC may represent an evolutionary adaptation to the greater bacterial load in the colon. The colon and the ileum should be regarded as separate entities, each comprising DC with distinct roles in mucosal immunity and imprinting.